Transmission ecology of Trypanosoma cruzi by Rhodnius prolixus (Reduviidae: Triatominae) infesting palm-tree species in the Colombian Orinoco, indicates risks to human populations. - Plutarco Urbano; Carolina Hernández; Natalia Velásquez-Ortiz; Nathalia Ballesteros; Luisa Páez-Triana; Laura Vega; Vanessa Urrea; Angie Ramírez; Marina Muñoz; Carlos N Ibarra-Cerdeña; Camila González; Juan David Ramírez (Public Library of Science (PLoS), 2024)
Background Chagas disease, affecting approximately eight million individuals in tropical regions, is primarily transmitted by vectors. Rhodnius prolixus, a triatomine vector, commonly inhabits in ecotopes with diverse palm tree species, creating optimal conditions for vector proliferation. This study aims to explore the transmission ecology of Trypanosoma cruzi, the causative parasite of Chagas disease, by investigating the feeding patterns and natural infection rates of R. prolixus specimens collected from various wild palm species in the Colombian Orinoco region. Materials and methods To achieve this objective, we sampled 35 individuals from three palm species (Attalea butyracea, Acrocomia aculeata, and Mauritia flexuosa) in a riparian forest in the Casanare department of eastern Colombia, totaling 105 sampled palm trees. DNA was extracted and analyzed from 115 R. prolixus specimens at different developmental stages using quantitative PCR (qPCR) for T. cruzi detection and identification of discrete typing units. Feeding preferences were determined by sequencing the 12S rRNA gene amplicon through next-generation sequencing. Results A total of 676 R. prolixus specimens were collected from the sampled palms. The study revealed variation in population densities and developmental stages of R. prolixus among palm tree species, with higher densities observed in A. butyracea and lower densities in M. flexuosa. TcI was the exclusive T. cruzi discrete typing unit (DTU) found, with infection frequency positively correlated with R. prolixus abundance. Insects captured in A. butyracea exhibited higher abundance and infection rates than those from other palm species. The feeding sources comprised 13 mammal species, showing no significant differences between palm species in terms of blood sources. However, Didelphis marsupialis and Homo sapiens were present in all examined R. prolixus, and Dasypus novemcinctus was found in 89.47% of the insects. Conclusion This study highlights the significance of wild palms, particularly A. butyracea, as a substantial risk factor for T. cruzi transmission to humans in these environments. High population densities and infection rates of R. prolixus were observed in each examined palm tree species.